Chronic fatigue syndrome: aetiology, diagnosis and treatment - Avellaneda Fernández, Alfredo; Pérez Martín, Álvaro; Izquierdo Martínez, Maravillas; Arruti Bustillo, Mar; Barbado Hernández, Francisco Javier; de la Cruz Labrado, Javier; Díaz-Delgado Peñas, Rafael; Gutiérrez Rivas, Eduardo; Palacín Delgado, Cecilia; Rivera Redondo, Javier; Ramón Giménez, José Ramón (BMC psychiatry, 2009)
Chronic fatigue syndrome is characterised by intense fatigue, with duration of over six months and associated to other related symptoms. The latter include asthenia and easily induced tiredness that is not recovered after a night's sleep. The fatigue becomes so severe that it forces a 50% reduction in daily activities. Given its unknown aetiology, different hypotheses have been considered to explain the origin of the condition (from immunological disorders to the presence of post-traumatic oxidative stress), although there are no conclusive diagnostic tests. Diagnosis is established through the exclusion of other diseases causing fatigue. This syndrome is rare in childhood and adolescence, although the fatigue symptom per se is quite common in paediatric patients. Currently, no curative treatment exists for patients with chronic fatigue syndrome. The therapeutic approach to this syndrome requires a combination of different therapeutic modalities. The specific characteristics of the symptomatology of patients with chronic fatigue require a rapid adaptation of the educational, healthcare and social systems to prevent the problems derived from current systems. Such patients require multidisciplinary management due to the multiple and different issues affecting them. This document was realized by one of the Interdisciplinary Work Groups from the Institute for Rare Diseases, and its aim is to point out the main social and care needs for people affected with Chronic Fatigue Syndrome. For this, it includes not only the view of representatives for different scientific societies, but also the patient associations view, because they know the true history of their social and sanitary needs. In an interdisciplinary approach, this work also reviews the principal scientific, medical, socio-sanitary and psychological aspects of Chronic Fatigue Syndrome.